Appearance of Pseudo-Pelger Huet Anomaly after Accidental Exposure to Ionizing Radiation in Vivo. Issue 3 (March 2015) - Goans, Ronald E.; Iddins, Carol J.; Christensen, Doran; Wiley, Albert; Dainiak, Nicholas
Abstract : Abstract: To evaluate the morphology of formed elements of human blood after exposure to ionizing radiation in vivo, archival smears of peripheral blood from eight individuals involved in the 1958 Y‐12 criticality accident at Oak Ridge, Tennessee, were examined manually by light microscopy. For each case, increased interlobar bridging was observed in nuclei of the myeloid cells, many of which were bilobed and morphologically similar to Pelger Huet (PH) cells. The high-dose group (n = 5, 2.98–4.61 Gy-Eq) exhibited 13.0 ± 0.85% PH cells (mean ± SEM) in the neutrophil population compared to 6.8 ± 1.6% in the low-dose group (n = 3, 0.29–0.86 Gy-Eq; p = 0.008). An age- and gender-matched control group (n = 8) exhibited 3.6 ± 0.9% PH cells. Results of a one-way ANOVA show that the high-dose group is statistically different from both the low-dose group and the control group ( p = 0.002). However, the low-dose group is not statistically different from the control group ( p = 0.122). The mean number of nuclear lobes in blood neutrophils was also enumerated as a function of time after exposure and was found to be diminished, consistent with incomplete nuclear segmentation that is characteristic of the Pelger Huet anomaly (PHA). In contrast to these changes in myeloid cells, the morphology of erythrocytes and platelets appeared to be normal. The authors conclude that ionizing radiation induces abnormal morphology of circulating neutrophils, which is similar to the pseudo-PHA that is acquired in disorders such as myelodysplastic syndrome, acute myeloid leukemia, and leukemoid reactions. Potential molecular mechanisms by which radiation induces this morphological change are discussed. From this cohort, the biomarker appears to be present early post-accident (<9 h) and stable at least up to 16 y post-accident. Assessment of circulating pseudo-Pelger Huet cells is being investigated as a potential biodosimetric tool.